Knowledge and attitude on social anxiety disorder among undergraduate students at the school of health sciences, USM - Kamil, Nurul Farah Shahira Ahmad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Knowledge on social anxiety disorder influence the attitude that shows the acceptance of people with social anxiety disorder. Less exposure to disorders including social anxiety disorder predicted endorsement of negative attitude. A cross-sectional study was conducted on 389 respondents recruited using a convenience sampling method. A validated questionnaire was given to all respondents that fit the inclusion criteria. The general objective of the study was to study the knowledge and attitude on social anxiety disorder among undergraduate students at the School of Health Sciences, USM. The level of knowledge and attitude on social anxiety disorder was analysed using a descriptive test. The association between knowledge with attitude on social anxiety disorder, and the association between socio-demographic data (age, gender, and race) with knowledge on social anxiety disorder was analysed using Chi-Square test. The findings of this study show that majority of undergraduate students at the School of Health Sciences, USM has moderate knowledge (n=276,71.0%) and positive attitude (n=363,93.3%) regarding social anxiety disorder. In this study, there is no significant association between knowledge with attitude on social anxiety disorder among undergraduate students at School of Health Sciences, USM (p-value=0.959). There is also no association between socio-demographic data (age, gender, and race) with knowledge on social anxiety disorder among undergraduate students at the School of Health Sciences, USM (pvalue= 0.078). Increasing the knowledge and attitude among students might help in better understanding of social anxiety disorder.